The Effects of Exercise on Patient-Reported Outcomes and Performance-Based Physical Function in Adults With Acute Leukemia Undergoing Induction Therapy: Exercise and Quality of Life in Acute Leukemia (EQUAL). (June 2018) - Bryant, Ashley Leak; Deal, Allison M.; Battaglini, Claudio L.; Phillips, Brett; Pergolotti, Mackenzi; Coffman, Erin; Foster, Matthew C.; Wood, William A.; Bailey, Charlotte; Hackney, Anthony C.; Mayer, Deborah K.; Muss, Hyman B.; et al.
Introduction . Fatigue is a distressing symptom for adults with acute leukemia, often impeding their ability to exercise. Objectives . 1) Examine effects of a 4-week mixed-modality supervised exercise program (4 times a week, twice a day) on fatigue in adults with acute leukemia undergoing induction chemotherapy. 2) Evaluate effects of exercise program on cognition, anxiety, depression, and sleep disturbance. 3) Evaluate effect of intervention on adherence to exercise. Methods . 17 adults (8 intervention, 9 control), aged 28-69 years, newly diagnosed with acute leukemia were recruited within 4 days of admission for induction treatment. Patient-reported outcomes (PROs) (fatigue, cognition, anxiety, depression, sleep disturbance, mental health, and physical health) and fitness performance-based measures (Timed Up and Go [TUG], Karnofsky Performance Status, and composite strength scoring) were assessed at baseline and at discharge. Changes in PRO and performance-based physical function measures from baseline to time of discharge were compared between groups using Wilcoxon Rank Sum tests. Results . With PROMIS (Patient-Reported Outcomes Measurement Information System) Fatigue, we found a median change in fatigue (−5.95) for the intervention group, which achieved a minimally important difference that is considered clinically relevant. Intervention group reduced their TUG performance by 1.73 seconds, whereas the control group remained fairly stable. A concerning finding was that cognition decreased for both groups during their hospitalization. 80% adherence of visits completed with a mean of 6 sessions attended per week. Conclusions . Our study provides information on the impact of exercise on symptomatology, with focus on fatigue and other psychosocial variables in acute leukemia.